2009
DOI: 10.1021/jp8114989
|View full text |Cite
|
Sign up to set email alerts
|

Role of Etching in Aqueous Oxidation of Hydrogen-Terminated Si(100)

Abstract: Surface infrared spectroscopy is used to examine the initial phases of oxidation of hydrogen-terminated Si(100) in ultrapure water containing dissolved oxygen. Analysis of both Si−O and Si−H vibrational modes suggests that oxide growth occurs in patches and reveals that much of the surface remains unoxidized after 5 h of immersion in O2(aq). Isotopic labeling experiments are used to demonstrate that the same type of surface etching that takes place in O2-free water occurs in the presence of O2(aq). Evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As is evident in Figure A, the initially sharp ν(SiH x ) bands broaden considerably after reaction with the carbenes, which renders integration of this peak, and therefore the calculated Si–H conversion, sensitive to small variations in the baseline; these values should therefore be considered as rough estimates. Additionally, some surface oxidation was observed for both 6 · Si(111) and 7 · Si(111) , which likely accounts for some of the decrease in surface SiH x species by replacement with surface SiOH or (SiO) 3 SiH species . The extent of surface oxidation, estimated by integration of the Si–O stretching bands in the two samples of each reaction type at ∼1000–1150 cm –1 (see the Supporting Information) and comparison with the intensity of the SiO 2 phonon signal from a chemical oxide, ranged from 28% to 33% of a full oxide layer after reaction with 7 and from 5% to 24% of a full layer after reaction with 6 .…”
Section: Si Wafer Studiessupporting
confidence: 81%
“…As is evident in Figure A, the initially sharp ν(SiH x ) bands broaden considerably after reaction with the carbenes, which renders integration of this peak, and therefore the calculated Si–H conversion, sensitive to small variations in the baseline; these values should therefore be considered as rough estimates. Additionally, some surface oxidation was observed for both 6 · Si(111) and 7 · Si(111) , which likely accounts for some of the decrease in surface SiH x species by replacement with surface SiOH or (SiO) 3 SiH species . The extent of surface oxidation, estimated by integration of the Si–O stretching bands in the two samples of each reaction type at ∼1000–1150 cm –1 (see the Supporting Information) and comparison with the intensity of the SiO 2 phonon signal from a chemical oxide, ranged from 28% to 33% of a full oxide layer after reaction with 7 and from 5% to 24% of a full layer after reaction with 6 .…”
Section: Si Wafer Studiessupporting
confidence: 81%
“…It has previously been reported [44][45][46][47] that vertically etching is mainly dependent on the type of silicon original crystallographic orientation, metal nanoparticles agglomeration on the surface of wafer and the competition among the etching rates in different silicon wafer planes. The top-view of the SEM image (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…90 At the same time, a recent study by Kulkarni et al shows that exposure of H-terminated silicon surface to aqueous oxygen at room temperature produces patches of surface oxide with a large amount of hydrogen still exposed. 91 Isotopic labeling indicated that etching plays a substantial role in surface oxidation.…”
Section: Chemical Reactivity and Selectivity Of The Modified Silicon ...mentioning
confidence: 99%